Geography school in basic education: approaches between Piauí state reality and municipality Alto Longa (PI) - Silva, Lineu Aparecido Paz e; Araújo, Raimundo Lenilde de; Lins, Cintia Dos Santos (Geosaberes; Vol 8 No 15 (2017): May - Aug, 2017)
This study aims to make a brief history about the geographic education in the State of Piauí, its evolution, the relationship with Geography Teaching and the teaching in Basic Education. Some factors stand out in the evolution of Teaching in the State of Piauí, among them the current conjuncture of the educational scenario in the State, the basic education teacher training courses, the evolution of education systems, investments in education, diversified didactic resources, The new technologies applied to education and the universalization of education. The history of education in geography in Piauí shows its evolution with emphasis on the training courses for Basic Education teachers, the transformation of education systems, investments in education, diversified didactic resources that changed the Piauí scenario in education
Keywords: Palavras Chave: Ensino de Geografia, Estado do Piauí, Alto Longá.